Kendala dan Strategi Peningkatan Layanan E-Samsat di Daerah Tertinggal - Nurfadilah, Ila; Saputra, Ondy Asep (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2025)
E-Samsat is a digital innovation in the vehicle tax payment system aimed at facilitating online tax services. While its implementation has shown success in urban areas, deploying E-Samsat in underdeveloped regions still faces numerous challenges, including limited technological infrastructure, low digital literacy among citizens, and weak inter-agency coordination. This study aims to identify key obstacles in E-Samsat implementation in remote regions and to formulate strategies for improving service effectiveness. Using a qualitative approach, this research employs literature review and interviews with local tax officials. The findings indicate that effective strategies include strengthening digital infrastructure, enhancing community education, developing user-friendly applications, and institutional integration. These insights are expected to serve as a guideline for local governments to expand the reach and quality of E-Samsat services in an inclusive and sustainable manner.